Ecological problems of technosphere and ways to overcome them - Кравченко, Я.О.; Краковський, В.В.; Вовк, О.О.; Шевчук, Н.А. (Proceedings of National Aviation University (archive), 2009)
The problem of environment protection from such two factors as energetic and industry is considered in the article. It is also proposed the ways of anthropogenic influence minimization, and namely: the improvement of industrial waste utilization system, and decreasing of green house gases emissions that are generated in power industry.